PISAH app monitors quarantined individuals due to Covid 19 - Nor Salwana, Mohammad Idris (2021)
PEKAN, 24 June 2021 - Since the Covid -19 outbreak began, various efforts have been enforced by the government in combating its spread in order to break the chain of infection.